Utilization of Social Media by Farming Community: A Case from Punjab State - Joshi, Divyata; Dhaliwal, R.K. (Indian Journal of Extension Education, 2019)
To equip the farmers with recent technologies, and innovations various tools of cyber extension are being used by the farming community, social media is one such area. To understand the utilization pattern of these social media tools used by farmers for agriculture purpose the study was conducted in Punjab state with fifty respondents (farmers) selected by simple random sampling technique. The data were collected through survey method using structured interview schedule. Two third of the respondents (66%), used YouTube always for agriculture related information. Majority of the respondents (52%) used PAU Kisan App ‘sometimes’ whereas 34 percent used it ‘always’ for getting information regarding agriculture, majority (58%) of the farmers posted queries on social media platforms. 68 per cent of the farmers contribute to discussions held in social media. Two third of the respondents (66%) shared agriculture information further on social media. Most of the farmers (74%) said that social media fulfills their information needs. Majority used social media for seeking information related to agriculture such as new varieties, trainings etc. Hence, it can be concluded that social media can be a new age solution to cater to the challenge of less availability of extension personnel by complementing the personnel for quick and effective dissemination of agriculture related information ultimately empowering farming community.
Keywords: Agriculture information; Credibility; Farming community; Social media; Utilization